Mechanical ventilation in neurocritical care patients: a systematic literature review. (2nd October 2016) - Borsellino, Beatrice; Schultz, Marcus J.; Gama de Abreu, Marcelo; Robba, Chiara; Bilotta, Federico
ABSTRACT: Introduction: Neurocritical care (NCC) patients often require prolonged mechanical ventilation, and they are at high risk of respiratory complications. Therefore, the potential benefit role of protective lung ventilation (PLV), which demonstrated to reduce postoperative complications in patients with acute distress respiratory syndrome, has been suggested even on NCC patients. However, PLV can increase intracranial pressure as result of permissive hypercapnia and of high airway pressures during recruitment maneuvers. The aim of this review (PROSPERO registration number: CRD42015027011) is to describe the ventilatory strategies, and in particular PLV, commonly used in NCC patients. Areas covered: We selected a total of 16 clinical studies, searching on PubMed and EMBASE databases, reporting original information on the MV on patients receiving NCC after acute brain injury, published in the last 10 years, in English language. Some of the included studies report data on a limited sample size. Expert commentary: The use of PLV techniques (PEEP, recruitment maneuvers, etc) in NCC patients is controversial. There is a wide variability among different centers in the treatment strategies and respiratory management of NCC patients, and there is the need for shared diagnostics and therapeutic studies, in order to improve the patients' outcome.